Engaging healthcare students in innovative approaches for antimicrobial resistance containment - Hassan Kasujja; Henry Kajumbula; Jonans Tusiimire; J. P. Waswa; Stella M. Nanyonga; Reuben Kiggundu; Daniel C. Mwandah; Marion Murungi; Nathan Mugenyi; Irene M. Mukenya; Mohan P. Joshi; Dan Schwarz; et al. (AOSIS, 2024)
No abstract available.